Case Report: Famotidine for Neuropsychiatric Symptoms in COVID-19 - Alper, Kenneth (Frontiers in Medicine, 2020)
Famotidine is of interest as a possible treatment for COVID-19, with effects on disease related symptoms and survival reported in observational and retrospective studies, as well as silico predictions of binding to putative SARS-CoV-2 drug targets. Published studies of famotidine for COVID-19 have focused on acute illness, and none have reported on neuropsychiatric symptoms. This case study reports on an 18-year-old man who sought psychiatric treatment for depression and anxiety, disruptive interpersonal conflicts, and impairments in attention and motivation following mildly symptomatic illness with COVID-19. The neuropsychiatric symptoms, which had been present for 16 weeks at the time of the initial evaluation represented a significant departure from the patient’s previous behavioral baseline. The patient had no prior psychiatric history preceding his illness with COVID-19, and no history of any prior treatment with psychopharmacological medications. Famotidine 20 mg twice daily by mouth was begun without any additional medications. At one-week follow-up the patient was much improved. Improvement was sustained through 12 weeks of follow-up during which the patient continued to take famotidine without apparent side effects. With progression of the COVID-19 pandemic it has become evident that persistent disease related symptoms may follow acute COVID-19 and may include neuropsychiatric symptoms. Controlled clinical research on famotidine for COVID-19 should follow, as well as the development of valid and reliable research diagnostic criteria to define and operationalize the features of a putative COVID-19 neuropsychiatric residual.